DEVELOPMENT OF A MULTIMEDIA-BASED MULTIMEDIA-BASED LEARNING MODEL FOR BASIC LOB FOREHAND BADMINTON BETTING TECHNIQUES IN TENTH CLASS STUDENTS 4 MEDAN STATE VOCATIONAL SCHOOLS - Dalimunthe, Rizki Jaharuddin; Ibrahim, Ibrahim (Journal of Physical Education, Health and Sports Recreation, 2023)
The problem that occurs in the learning process is the need for interesting and fun media so that it can build student motivation and make it easier for students to carry out the basic techniques of playing badminton. This research aims to produce a product in the form of an animated video and a guide book. The learning process is carried out using multimedia-based media. Learning media for basic forehand lob techniques for class ten at SMK Negeri 4 Medan. This research method is research and development (Research and Development sugiono), which uses eight steps in development research. With a small scale respondent of 10 students and a large scale trial of 20 students. Based on expert validation of the multimedia-based basic badminton lob forehand technique learning model for vocational high school students including 93.75% material experts and 90% media experts. Small scale trial feasibility was 74.12%. Large-scale trial feasibility was 88.43%. Overall, the learning media model for learning the basic techniques of badminton forehand lob strokes based on multimedia for class X students at SMK Negeri 4 Medan is very suitable for use after going through several trial stages.